2019
DOI: 10.5430/jha.v8n1p50
|View full text |Cite
|
Sign up to set email alerts
|

Hospital value based purchasing scores highly associated with prior year score and organizational characteristics

Abstract: Objective: Medicare’s Hospital Value Based Purchasing program (HVBP) rewards hospitals which achieve a higher than mean Total Performance Score (TPS). This article investigates the relationship between hospital characteristics and prior year Total Performance Score (TPS) on current year TPS under Medicare’s Hospital Value Based Purchasing (HVBP) program.Methods: Regression analyses are used to investigate the relationship between prior year TPS and organizational characteristics on current year TPS.Results: Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…This suggests the highest performing hospitals, with presumed excellence in processes and outcomes, can maintain their status year after year and prevent others from increasing in rank. This is supported by recent research which found prior‐year TPS is the most significant predictor of current year TPS 10 . And may suggest lower performers cannot increase their rank easily, despite earning points for improvement over self.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…This suggests the highest performing hospitals, with presumed excellence in processes and outcomes, can maintain their status year after year and prevent others from increasing in rank. This is supported by recent research which found prior‐year TPS is the most significant predictor of current year TPS 10 . And may suggest lower performers cannot increase their rank easily, despite earning points for improvement over self.…”
Section: Introductionsupporting
confidence: 64%
“…It is also possible that the expense associated with improving TPS is greater than the lost revenue for some hospitals, particularly as certain hospital characteristics are associated with TPS. 8,9,10,16 A qualitative study would be needed to explore this assertion. Last, the transitory probability analyses only included the Top and Bottom 5% of hospitals, while this limits generalizability, it did demonstrate that the extremes in scores were not static.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations